2013
DOI: 10.23986/afsci.8160
|View full text |Cite
|
Sign up to set email alerts
|

Slow-release fertilizer to increase grain N content in spring wheat

Abstract: Low grain protein often restricts the use of grain lots for milling in Finland. Nitrogen availability during grain-filling may restrict grain protein accumulation, particularly in high yielding environments. Slow-release fertilizers could potentially sustain nitrogen availability during the grain-filling period. The aim of this study was to increase plant nitrogen uptake, grain yield and grain protein response of spring wheat cultivar ‘Amaretto’, using combinations of a regular and slow-release compound NPK fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…In this study, the optimal ratio of SRU to CU in the rice season was higher than that in the wheat season, perhaps because sufficient availability of water and heat in the rice season are conducive to the release and transport of SRU nutrients and the decomposition of the residue of the previous crop, allowing higher ratios of SRU to CU [24,25]. However, the low temperature and low rainfall in the wheat season are not conducive to the release of SRU and the decomposition of crop residue, so higher ratios of CU to SRU is generally required to meet the demand for nitrogen by crop residue decomposition and wheat growth in the early growth stage [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the optimal ratio of SRU to CU in the rice season was higher than that in the wheat season, perhaps because sufficient availability of water and heat in the rice season are conducive to the release and transport of SRU nutrients and the decomposition of the residue of the previous crop, allowing higher ratios of SRU to CU [24,25]. However, the low temperature and low rainfall in the wheat season are not conducive to the release of SRU and the decomposition of crop residue, so higher ratios of CU to SRU is generally required to meet the demand for nitrogen by crop residue decomposition and wheat growth in the early growth stage [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…The N release of the SF agrees with the crop nutrient requirement, allowing for the coordination of vegetative and reproductive growth, a reduction in nutrient loss, an improvement in N utilization efficiency and a reduction in topdressing labor costs [ 19 ]. In the past decade, studies on rice [ 20 , 21 , 22 , 23 , 24 ] and wheat [ 25 , 26 , 27 , 28 , 29 ] have reported that the application of SF affects the grain quality by changing the concentrations of protein, starch, oil and mineral elements. However, studies have mainly focused on the grain quality while starch structural and functional properties have received less attention [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lower N availability reduced plant N-content at heading stage. Lower grain and straw N-content and lower plant N-uptake indicate lower N-availability also at grain filling period, (Rajala and Peltonen-Sainio (2013).…”
Section: Introductionmentioning
confidence: 99%